A Retrospective Review of the Effect of COVID-19 Pandemic on Laboratory Utilization. (28th October 2021) - Olayinka, O; Odujoko, O; Barasch, S; Farley, J; Woodruff, C; Chan, S
Abstract: Introduction/Objective: We performed a retrospective analysis of test volumes in clinical pathology prior to and during the COVID-19 pandemic to better understand the impact of the pandemic on our laboratory utilization. Methods/Case Report: The laboratory information system was queried for test order volume in 2019 and 2020 using Discern Analytics 2.0. Representative tests including C-reactive protein (CRP), D-dimer, fibrinogen, ferritin, lactate dehydrogenase (LDH), procalcitonin, prothrombin time (PT), point of care iSTAT blood gas analysis, ABO and Rhesus typing (ABORh), antibody screening, flow cytometry, and serum protein electrophoresis (SPEP). Data was analyzed using Microsoft Excel 2013. Results (if a Case Study enter NA): The data showed an increase in the number of tests ordered and verified in the in-patient setting. The increase was most substantial for D-dimer, CRP and LDH with a percentage increase of approximately 200% on each test from year 2019 to 2020. An increase of 73% and 57% was noted for ferritin and fibrinogen respectively. A slight decrease in volume was noted for tests ordered in the out-patient setting including SPEPs during the pandemic. There was no significant change in the number of orders verified for point of care ISTAT blood gas testing between 2019 and 2020. Procalcitonin test volume increased steadily from its implementation in May 2020 with a steep rise in test volume in November and December. A total of 75, 295 SARS-CoV-2 molecular tests were ordered between March and December 2020 with approximately 80% of the orders being performed as a send- out test. Conclusion: The COVID-19 pandemic has had a substantial impact on laboratory utilization with significant volume increases in tests that guide the management of hospitalized COVID-19 patients and slight decrease in tests ordered mostly in the outpatient setting. These results may help guide current and future decisions relating to laboratory operations during pandemics.